ABUNDANCE OF Anabaena azollae AND NITRATE LEVELS IN Azolla microphylla BRACKISH WATER CULTURE - Nursyafni Nanggola; Irwan Effendi; Nursyirwani Nursyirwani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Azolla michrophylla is beneficial for Anabaena azollae because it can act as a host through the supply of oxygen and nitrogen that can be used. Nitrogen fixation carried out by A. Azollae is atmospheric nitrogen gas (N2) converted into ammonia (NH3). This research was conducted at the Laboratory of Marine Microbiology and Marine Chemistry, Department of Mariene Science, Faculty Of Fisheries And Marine Science, University of Riau in April to June 2018. The purpose of this research was to determine the abundance of A. azollae in the growth of A. microphylla plants and determine the levels of nitrate contained in the growth of A. microphylla in brackish water culture. Factorial randomized group design (RAK) was applied in this experimental. Temperature, salinity, and pH were water quality parameters measured. The results showed that the best growth of A. microphylla was obtained at a salinity of 0 ppt with a starter of A. microphylla 3 gram with a value of 50.42 gram. The highest abundance of A. azollae is found in salinity 3 ppt with a 3 gram level with the abundance of 5643 cells / ml. A. microphylla and A. azollae had sufficient nitrate levels for their growth in brackish water cultured at 0, 1, 2, and 3 ppt salinitis of in combination with A. microphylla 1, 1.5 and 3 gram as a starters. The highest nitrate level was obtained on the 14th and 21st day with a value of 1.2625 mg / L and 1.4500 mg / L. Keywords: Azolla microphylla, Anabaena azollae, Growth, Abundance, Nitrate.